2020
DOI: 10.1042/bsr20191194
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA FENDRR inhibits migration and invasion of cutaneous malignant melanoma cells

Abstract: The present study aimed to investigate the effects of lncRNA FENDRR on the migration and invasion of malignant melanoma (MM) cells. The expression levels of FENDRR in MM tissues and MM cell lines were detected using qRT-PCR, followed by construction of FENDRR-knocked down and overexpressed stable cells. Then the effects of FENDRR on cell proliferation, migration and invasion were detected using MTT assay and Transwell assay. The protein expression levels of matrix metallopeptidase 2 (MMP2), MMP9, and related f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A similar story emerged when we compared lncRNA enriched with SFPQ in PM and melanoma cell backgrounds. The SFPQenriched lncRNA transcripts most specific to PM were EMX2OS and FENDRR, the latter reported to function as a tumour suppressor in most cancers, including melanoma [27,[46][47][48][49]. The function of EMX2OS in cancer differs depending on cell background [28,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar story emerged when we compared lncRNA enriched with SFPQ in PM and melanoma cell backgrounds. The SFPQenriched lncRNA transcripts most specific to PM were EMX2OS and FENDRR, the latter reported to function as a tumour suppressor in most cancers, including melanoma [27,[46][47][48][49]. The function of EMX2OS in cancer differs depending on cell background [28,50].…”
Section: Discussionmentioning
confidence: 99%
“…Discerning the functional importance of enriched lncRNA gene lists from RNA-seq studies such as the one reported here is problematic, as the vast majority of lncRNAs remain functionally uncharacterised. However, it is interesting to note that the most PM-specific SFPQ-lncRNA interactors included genes associated with tumour suppressor function, such as EMX2OS and FENDRR [27,28], whereas the most A2058-specific SFPQ-lncRNA interactors comprise genes widely reported as oncogenic, such as LINC00511 [29][30][31]. We next sought to validate the top hits from our A2058 RIP-seq data in additional melanoma cell lines.…”
Section: Sfpq Knockdown Decelerates Cancer Cell Phenotype In Melanomamentioning
confidence: 99%
“…FENDRR is a long noncoding RNA located on chr3q13.31. Studies have shown that FENDRR is low expressed in a variety of tumor tissues and can inhibit tumor progression ( 26 , 27 ). However, the role of FENDRR in the development of OSCC is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA forkhead box D3 antisense RNA 1 was previously discovered to increase CMM cell proliferation, invasion and migration by regulating the miR-325/mitogen-activated protein kinase kinase kinase 2 axis ( 11 ). In addition, the lncRNA FOXF1 adjacent non-coding developmental regulatory RNA was reported to inhibit the migration and invasion of CMM cells ( 12 ). The lncRNA TINCR ubiquitin domain containing (TINCR) was also found to function as a tumor suppressor in various types of cancer.…”
Section: Introductionmentioning
confidence: 99%